Characterization of Minerals, Metals, and Materials 2017 - Ikhmayies, Shadia; Li, Bowen; Carpenter, John S.; Li, JIan; Hwang, Jiann-Yang; Monteiro, Sergio Neves; Firrao, Donato; Zhang, Mingming; Peng, Zhiwei; Escobedo-Diaz, Juan P.; Bai, Chenguang; Kalay, Yunus Eren; et al. (The Minerals, Metals & Materials Series,, 2017)
This collection gives broad and up-to-date results in the research and development of materials characterization and processing. Coverage is well-rounded from minerals, metals, and materials characterization and developments in extraction to the fabrication and performance of materials. In addition, topics as varied as structural steels to electronic materials to plant-based composites are explored. The latest research presented in this wide area make this book both timely and relevant to the materials science field as a whole. The book explores scientific processes to characterize materials using modern technologies, and focuses on the interrelationships and interdependence among processing, structure, properties, and performance of materials. Topics covered include ferrous materials, non-ferrous materials, minerals,ceramics, clays, soft materials, method development, processing, corrosion, welding, solidification, composites, extraction, powders, nanomaterials, advanced materials, and several others.